On Efficiency and Duality for Multiobjective Variational Problems - Mishra S.K.; Mukherjee R.N. (My University, 2025)
The concept of efficiency (Pareto optimum) is used to formulate duality for multiobjective variational problems. Wolfe and Mond-Weir type duals are formulated. Under generalized (F, ρ) - convexity assumptions on the functions involved weak and strong duality theorems are proved. © 1994 Academic Press, Inc.